Pengaruh Penggunaan Brand Ambassador dan Diskon Terhadap Minat Beli Konsumen di Marketplace Shopee - Gusva Nanda Prayoga; Mirzam Arqy Ahmadi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The development of the current digital era has an impact on all aspects. Not only in the economic sector but also in the field of online sales or e-commerce also feels the impact. Because technological knowledge continues to grow, every consumer must be able to follow developments that affect their daily needs. Online marketplaces such as Shopee have become shopping platforms for consumers today. This study uses a quantitative approach, where the population consists of Shopee marketplace users. The purpose of this study is to determine the effect of brand ambassadors and discounts on purchasing interest. And the technique used in this study is the Non-Probability Sampling technique. By using SmartPLS version 3 software to analyze data with the Partial Least Square (PLS-SEM) method. This study shows that brand ambassadors and discounts have a positive and significant influence on purchasing interest.